Durabilitas Mortar Bubuk Kulit Kerang Di Air Gambut - Ismi Siska Rahmayani; Monita Olivia; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In this study, blood clam used as filler in mortar. The specimens were cured in distilled water until 28 days. Then specimens were immersed in peat water until 91 days. The parameters studied include compressive strength and porosity. These properties were compared with those of a control mortar that was made of Ordinary Portland Cement (OPC). The main parameter of this study was the proportion of waste blood clam (4% by cement weight). The results showed that the compressive strength of mortar with blood clam are increase more than mortar OPC. Mortar becomes more resistant because it was filled by the blood clam.Keywords: blood clam, durability, filler in mortar, peat water, compressive strength, porosity